Algal biotechnology for bioenergy, environmental remediation and high-value biochemicals - Abdullah, M.A. (Apple Academic Press, 2014)
Algae are one of the most primitive life forms and most abundant on earth. They consist of one or more of eukaryotic cells containing chlorophyll. It may be a single cell, colonies, filament of cells, or as in the kelp, simple tissues. The cell doubling time is typically 1-2 days, and under optimal conditions can be as short as 6 hours for reported in Chlamydomanas species (Chen et al., 2009), as compared to bacteria (20 min), animal cells (20 hours) and plant cells (2-4 days). Algae inhabit particularly the oceans, rivers, lakes, streams, ponds and swamps, but some species can be found in the soil and survive dry conditions for a long time. Because of such diverse ecological habitats ranging from seawater, freshwater or brackish water, they are equipped to flourish in extreme temperature and pHs such as at 80Â°C, in and around hot springs, or in the snow and ice of Arctic and Antarctic regions (Rosenberg et al., 2008). In the tropics and subtropics, algae may be found on leaves, woods and stones, within or on plants and animals. Although for many years categorized as plants because of their photosynthetic ability, algae are now placed within the diverse kingdom Protista of eukaryotic, predominantly single-celled microscopic organisms (Hollar, 2012). Â© 2015 by Apple Academic Press, Inc.